Technological Innovation of China′s Rail Transit Equipment and Its Value Evaluation from the Perspective of Patents - XIE Aiqing; REN Shengce (Chengshi guidao jiaotong yanjiu)
［Objective］ As an important yardstick for measuring technological innovation capabilities, patent is of great significance to the innovative development of rail transit equipment. Currently, the systematic evaluation of patent value in the field of rail transit equipment in China is still insufficient, and it is necessary to make an in-depth analysis of its innovation trends and value. ［Method］ The required patent data information is retrieved from the Dawell Innojoy Global Patent Database. Statistical methods are utilized to conduct an analysis of technological innovation in general and an analysis of the technological composition and evolution of patents in the field of rail transit equipment in China. Four patent indicators are adopted to evaluate the patent value of major applicants and technological fields based on the principal component analysis method. ［Result & Conclusion］ The technological innovation in China′s rail transit equipment presents a growing trend, but the collaboration needs to be improved. The direction of computational methods among the major technology categories is booming along with the wave of digitalization. High-value patents are distributed in the major technological fields, where universities hold patents of basically higher value as a whole than those enterprises do. The development trend of technological innovation in the field of rail transit equipment in China is steadily positive. In the future, the direction of high-value technological innovation can be the focus, and the cooperation among universities, enterprises and research institutions in production, education and research can be further deepened.